Relevansi Muatan Materi Sastra dalam Buku Teks Bahasa Indonesia SMP Kurikulum Merdeka dengan Profil Pelajar Pancasila - Dewi Anggraini; Yang Yang Merdiyatna (Pendidikan Bahasa dan Sastra Indonesia, 2025)
The Merdeka Curriculum emphasizes learning flexibility, student differentiation, and character development through the implementation of the Pancasila Student Profile. In this context, textbooks play an essential role as a medium for shaping values, knowledge, and skills. Literary works in Indonesian language learning function not only as reading materials but also as media for developing moral and aesthetic sensitivity. This study aims to analyze the literary content in the Grade VIII Indonesian language textbook of the Merdeka Curriculum and its relevance to the six dimensions of the Pancasila Student Profile. Using a qualitative approach and content analysis method on two short stories and eight poems, the results show that 53 out of 184 pages (28.80%) contain literary materials. The literary texts contribute to fostering students’ sense of humanity, faith, and creativity. The most dominant dimensions represented are “Faith in God Almighty and Noble Character” and “Creativity,” while “Mutual Cooperation” and “Global Diversity” are less represented.